Geographically Resolved Rhythms in Twitter Use Reveal Social Pressures on Daily Activity Patterns - Leypunskiy, Eugene; Kiciman, Emre; Shah, Mili; Walch, Olivia J.; Rzhetsky, Andrey; Dinner, Aaron R.; Rust, Michael J. (Current Biology, 2018)
Daily rhythms in human physiology and behavior are driven by the interplay of circadian rhythms, environmental cycles, and social schedules. Much research has focused on the mechanism and function of circadian rhythms in constant conditions or in idealized light-dark environments. There have been comparatively few studies into how social pressures, such as work and school schedules, affect human activity rhythms day to day and season to season. To address this issue, we analyzed activity on Twitter in >1,500 US counties throughout the 2012–2013 calendar years in 15-min intervals using geographically tagged tweets representing ≈0.1% of the total population each day. We find that sustained periods of low Twitter activity are correlated with sufficient sleep as measured by conventional surveys. We show that this nighttime lull in Twitter activity is shifted to later times on weekends relative to weekdays, a phenomenon we term “Twitter social jet lag.” The magnitude of this social jet lag varies seasonally and geographically—with the West Coast experiencing less Twitter social jet lag compared to the Central and Eastern US—and is correlated with average commuting schedules and disease risk factors such as obesity. Most counties experience the largest amount of Twitter social jet lag in February and the lowest in June or July. We present evidence that these shifts in weekday activity coincide with relaxed social pressures due to local K-12 school holidays and that the direct seasonal effect of altered day length is comparatively weaker.